PERAN MEETING OF ASEAN TOURISM MINISTERS (M-ATM) DALAM PEMULIHAN SEKTOR PARIWISATA DI INDONESIA AKIBAT PANDEMI COVID-19 - Ilyasa Chairul Nurahman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research analyzed the role of Meeting of ASEAN Tourism Ministers (M-ATM) toward the recovery of the tourism sector in Indonesia as a result of the covid-19 pandemic. Tourism is an important sector for the development of a country facing new challenges resulting from the COVID-19 pandemic, and tourism is one of the most affected sectors. The research use qualitative methods, using technical document analysis data from international and national journals, books, official issues of institutions, and twitter with the level of group analysis. To analyze the role of the Meeting of ASEAN Tourism Minister (M-ATM) in the restoration. This research uses the institutional liberalism perspective and international organizational theory. The result of the study indicates that the Meeting of ASEAN Tourism Minister (M-ATM) played a significant role in the recovery of the tourism sector in Indonesia and the ASEAN region affected by the COVID-19 pandemic. Through M-ATM, Indonesia can strengthen and accelerate the recovery of the tourism sector through cooperation, information exchange, hygiene protocol development and joint promotion in the ASEAN region. Keywords: ASEAN, M-ATM, Tourism, COVID-19 Pandemic